ANALISA PENGENDALIAN RISIKO KERJA PREVENTIVE MAINTENANCE SINGLE POINT MOORING DENGAN METODE RISK ASSESMENT - Yuliana Isnani; Achmad Kusairi Samlawi (JTAM ROTARY, 2019)
This study aims to determine the working risk of preventive maintenance Single Point Mooring and to determine the existing risk control on preventive maintenance activities Single Point Mooring in PT. Pertamina RU-V Balikpapan. This research is a qualitative descriptive research with observasional approach. The method used is case study on PT. Pertamina RU-V Balikpapan. Data obtained through observation, interview, and documentation. The validity of data is done by membercheck method, and data analysis using semi quantitative risk assesment with AS/NZS 4360 Standard. The results showed (1) the percentage of working risk of Single Point Mooring preventive maintenance activity using risk assesment method shows 29,41% low risk, 64,70% medium risk, and 5,88% high risk. (2) 6 risk controls methods are elimination, substitution, engineering control, isolation, administration control and personal protective equipment. The dominant control method used is the metod of personal protective equipment and administration control. The prevention of occupational injuries addressed to the environment of machines, work equipment, and especially human factors